Clusterisation Processes in the Hungarian Automotive Industry - Grosz, András (Discussion Papers, 2012)
The author of this paper is going to follow clusterisation processes in the field of Hungarian automotive industry having traditional fundaments in Northwest-Hungary, whose development has been accelarated by the emergence of foreign direct investments and the specialisation of automotive services from the early 90’s. After a short review of international literature (clusterisation and cluster development policy) and the automotive sector with its supporting and linking industries as a cluster, the paper investigates the major features of the spatial concentration of the sector in Hungary, the progress of supplier relations, the role of innovation, research-development and training in the automotive sector and the factors fostering clusterisation process. For the exploration of the competitive advantage of automotive sector Porter’s diamond model is used. Finally the study deals with the first Hungarian cluster initiative called PANAC, which focuses as a cluster development tool on the increase of the competitiveness of the Hungarian automotive sector. The author diagnoses that in Hungary we can’t speak about a well developed automotive cluster yet, however the critical mass of the sector and its supporting industry, the tradition in mechanical engineering and the existing university capacities and competences make it a potential automotive cluster, in which well focused development policy can obtain significant results in the mid-term.